THE ACMEOLOGICAL APPROACH TO DEVELOPING THE CREATIVITY OF FUTURE SPECIALISTS - Bakriddinov Dostonbek Bakhtiyor oglu (Bright Mind Publishing, 2026)
This article examines the role of the acmeological approach in developing the creativity of future specialists within the higher education system. Acmeology, as a science of personal and professional development, focuses on achieving the highest level of individual potential. The study highlights the pedagogical significance of acmeological principles in fostering creative thinking, self-development, and professional competence among students. The article analyzes theoretical foundations of the acmeological approach and identifies effective pedagogical conditions for enhancing creativity in future specialists. The results emphasize that integrating acmeological strategies into the educational process contributes to the formation of competitive, innovative, and self-realized professionals.
Keywords: Acmeology, creativity development, future specialists, professional competence, creative thinking, higher education.